FEATURES OF PERSONAL PSYCHOCORRECTION OF FUTURE PSYCHOLOGISTS IN THE PROCESS OF PREPARATION TO WORK WITH ANXIOUS ADOLESCENTS - Iryna Drobotko (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article describes the peculiarities of professional preparation of prospective psychologists in higher educational institutions, defines needs to practice personal psychological correction during professional educational process and determines the essence and content of psychological correction. It distinguishes the main components of professional readiness of prospective specialists for correctional influence: theoretical (knowledge of theoretical fundamentals and methods of correctional work), practical (knowledge of correctional methods and techniques), personal readiness (psychological solving of personal problems in the spheres to be corrected while working with the client). The article presents the criteria for the personal correction: a deep understanding of one's own unconscious sphere and personal characteristics, the acceptance of life position and the world, the formation of humanist values; it summarizes the consequences of psychologists' lack of correction in their practical activity. It determines the meaning of the notion «lack of correction» (burden of personal problems (inner conflict), causing personal destructions in case these problems are unsolved), explains the main differences of a person who undergoes psychological correction. The article describes the difficulties of prospective psychologists' work with teenagers with anxiety and analyses personal destructions of the subjects of social and psychological training as well as the techniques of deep cognition of personality. It explains the appropriateness of deep personal psychocorrection in preparation of prospective psychologists in higher educational institutions for helping teenagers with anxiety. The article suggests the pattern of preparation of prospective psychologists for helping teenagers with anxiety and defines the conditions of prospective specialists' involvement to personal psychocorrection that include three stages: organizing-preparatory, educational-corrective and operative- reflective.